Actualización de la gestión de mantenimiento para el cumplimiento de la norma ISO 9001 - Solano-Cervantes, Erik (Instituto Tecnológico de Costa Rica, 2017)
This project was developed in Smith-Sterling, whose main activity is the design and manufacture of dental restorations. The objective of the present study was to update maintenance management in a way that would allow the Maintenance Department to comply with ISO 9001 standards. This was achieved by establishing a series of proactive actions, which reduce the time lost by the functional failures of the gear and implementing an index system that allows the continuous improvement of the department. The process to implement a preventive maintenance plan was initiated with a criticality analysis to select the equipment to be included in the program, based on criteria such as operational flexibility, failure rate, repair cost, among others. After knowing the equipment to study, it was decided to use the RCM methodology, present in SAE JA1011 and SAE JA1012. Assets were investigated to find out which were the most recurring fault modes, causes and effects of these, and proposed, together with a work group conformed of company personnel, a set of actions to improve the availability of machines. Based on these actions, the frequency of their implementation and the assignment of work to maintenance personnel, a preventive maintenance manual was created. After elaborating the maintenance plan, a system of indicators based on the Balanced Scorecard methodology was proposed. As part of the design of this system, a SWOT analysis and a strategic map were carried out to identify areas for improvement. Objectives were focused on perspectives such as learning, internal processes, finances and clients, leading to the selection of thirteen indicators that evaluate the impact of the department's management within the company. Finally, a database was designed in Microsoft Access and a study of manpower was carried out, based on the methodology present in the book Management of projects of industrial assets of Luis Amendola, that allowed to calculate the suitable amount of technicians with whom the maintenance department must count.
Proyecto de Graduación (Licenciatura en Mantenimiento Industrial) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electromecánica, 2017.
Keywords: Gestión; Mantenimiento; Flexibilidad operacional; RCM; FODA